Analysis of the Implementation of School Values ​​in Enhancing Positive Culture at SMK Pariwisata Metland School - Tiraswati, Dina Martha; Dwiningrum , Siti Irine Astuti (Jaanur Elbarik Indonesia, 2025)
This study aims to analyze the implementation of school values ​​in enhancing a positive culture and identify supporting and inhibiting factors. The research method uses a descriptive quantitative approach supported by qualitative analysis through observation, interviews, and documentation studies with correlation and regression analysis. The results of the study indicate that the success of the implementation of school values ​​is influenced by three main aspects: value-based school governance, integration of values ​​in the learning process, and role models and habits through the school environment. These findings confirm that the implementation of values ​​cannot be effective without the support of a managerial system, teacher consistency, and active student participation. This article contributes to the development of a model for the implementation of school values ​​that can be a reference for vocational schools in building a sustainable positive culture.